2019
DOI: 10.1093/mnras/stz1215
|View full text |Cite
|
Sign up to set email alerts
|

Three years of Sun-as-a-star radial-velocity observations on the approach to solar minimum

Abstract: The time-variable velocity fields of solar-type stars limit the precision of radial-velocity determinations of their planets’ masses, obstructing detection of Earth twins. Since 2015 July, we have been monitoring disc-integrated sunlight in daytime using a purpose-built solar telescope and fibre feed to the HARPS-N stellar radial-velocity spectrometer. We present and analyse the solar radial-velocity measurements and cross-correlation function (CCF) parameters obtained in the first 3 yr of observation, interpr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 44 publications
8
110
1
Order By: Relevance
“…Using the solar telescope (Phillips et al 2016) operating with the HARPS-N spectrograph at the Telescopio Nazionale Galileo (TNG, Cosentino et al 2012), we extract high-resolution disk-integrated solar spectra (Dumusque et al 2015). We now have more than 50,000 high-SNR solar exposures spanning over 4 years of observing (Collier Cameron et al 2019). In this work, we apply Meunier's methods to the first 2.5 years of the solar dataset (from Summer 2015 -November 2017) to attempt a recovery of a precise value of α for use in reconstructing RV conv and RV sppl .…”
Section: Introductionmentioning
confidence: 99%
“…Using the solar telescope (Phillips et al 2016) operating with the HARPS-N spectrograph at the Telescopio Nazionale Galileo (TNG, Cosentino et al 2012), we extract high-resolution disk-integrated solar spectra (Dumusque et al 2015). We now have more than 50,000 high-SNR solar exposures spanning over 4 years of observing (Collier Cameron et al 2019). In this work, we apply Meunier's methods to the first 2.5 years of the solar dataset (from Summer 2015 -November 2017) to attempt a recovery of a precise value of α for use in reconstructing RV conv and RV sppl .…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have a strong impact for the exoplanet community, for both detectability and mass characterization, but also in stellar physics: for example, the hysteresis in the relationship between RV and log R HK is indicative of the sign of the dynamo wave, provided the inclination is known. This is complementary to other approaches, for example MHD simulation of granulation (Cegla et al 2018), or the direct observation of solar integrated RV: many groups have indeed recently implemented dedicated instruments to be able to observe the integrated RV of the Sun as a star, for example with HARPS-N in La Palma (Dumusque et al 2015;Collier Cameron et al 2019), HARPS at the 3.60m in La Silla, Espress at Lowell Observatory. Based on the results obtained in the fitting challenge presented in Dumusque et al (2017) and our simulations, we found that given current mitigating technique of stellar activity, Earth mass planet in the habitable zone around solar type stars is not possible, except for K stars observed in very good conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The changing flux ratio between thorium and argon emission lines of the dying ThAr lamp induced a 2 m s −1 day −1 drift in the wavelength solution of HARPS over 5 days. The problematic data were confirmed by comparing unpublished data from the HARPS-N solar telescope (Dumusque et al 2015;Collier Cameron et al 2019) and Helios on HARPS, which also observes the Sun daily. The Helios RVs show a clear drift away from the RVs from the HARPS-N solar telescope 25 -27 November 2018, before returning to a nominal level after the change of the ThAr lamp.…”
Section: High Resolution Spectroscopy With Harpsmentioning
confidence: 91%